Analysis of Mathematical Reasoning Ability Viewed from Mathematical Logical Intelligence Middle School Students - Selly Meilina Arifin; Ayu Tsurayya (Budapest International Research and Critics University, 2022)
Reasoning is one of parts most important in of learning math. However still many students which still confused do problems math especially in questions story SPLDV which really need ability reasoning. For that in research aims to analyze ability reasoning in mathematical terms of intelligence logical mathematical school junior hig research is research study case approach this Subjects in research are this 3 students’ class VIII SMPN 188 Jakarta consists of students who have level intelligence logical high moderate and low. The collection data in research this carried outiwith method test, interview and documentation Based on results analysis data ithat obtained iwho student has high level intelligence logical mathematicali) S1ifulfills all indicators ability reasoning mathematical in third( questions, student who has level intelligence logical mathematical moderate (S2) only fulfills four indicators ability reasoning mathematical student tin the qand third iwhich has level intelligence logical is low only fulfills three indicator on question number one then, only two indicators for question number two and three.